2017
DOI: 10.1007/s10802-017-0289-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Executive Functioning and Scaffolding in Families of Children with and without Parent-Reported ADHD

Abstract: Parental scaffolding robustly predicts child developmental outcomes, including improved self-regulation and peer relationships and fewer externalizing behaviors. However, few studies have examined parental characteristics associated with a parent's ability to scaffold. Executive functioning (EF) may be an important individual difference factor associated with maternal scaffolding that has yet to be examined empirically. Scaffolding may be particularly important for children with attention-deficit/hyperactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 62 publications
1
19
1
Order By: Relevance
“…Contrary to our expectations, parental EF was not significantly associated with parents' general parenting practices after controlling for child age and gender, family income, and parental education. This finding is surprising in light of prior research indicating relations among parental self-regulation and EF capacities and their caregiving practices (e.g., Deater-Deckard et al, 2010;Deater-Deckard & Bell, 2017;Mazursky-Horowitz et al, 2018;Shaffer & Obradovic, 2017). There are several possible explanations for the null findings.…”
Section: Parental Ef General Parenting Practices and Ef-specific contrasting
confidence: 70%
See 2 more Smart Citations
“…Contrary to our expectations, parental EF was not significantly associated with parents' general parenting practices after controlling for child age and gender, family income, and parental education. This finding is surprising in light of prior research indicating relations among parental self-regulation and EF capacities and their caregiving practices (e.g., Deater-Deckard et al, 2010;Deater-Deckard & Bell, 2017;Mazursky-Horowitz et al, 2018;Shaffer & Obradovic, 2017). There are several possible explanations for the null findings.…”
Section: Parental Ef General Parenting Practices and Ef-specific contrasting
confidence: 70%
“…Parents with poorer EF skills may have difficulty inhibiting their prepotent responses (e.g., yelling) in response to a frustrated child's behaviour. Similarly, when engaging their child in a learning task, parents may have to call upon their EF in order to stay on task (e.g., inhibitory control), remember the rules (e.g., working memory), and not get distracted (e.g., attentional flexibility) in a demanding environment (Barrett & Fleming, 2011;Bridgett, Burt, Edwards, & Deater-Deckard, 2015;Crandall, Deater-Deckard, & Riley, 2015;Mazursky-Horowitz et al, 2018).…”
Section: Parental Ef and Parenting Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most parenting involves reinforcement that is delayed (e.g., ignoring a child’s crying in the moment to work toward a longer-term goal of extinguishing tantrum behaviors), or inconsistent (a child thanks the parents only infrequently), and involves consequences that may not be particularly rewarding to the parent; this makes many aspects of successful parenting particularly challenging for individuals with ADHD-related motivation difficulties. Moving forward, emotion regulation, motivational processes, and cognition should be examined concurrently in studies of parenting in ADHD to assess their individual and collective impact on parenting behavior and treatment outcome, given their interplay (Deater-Deckard et al 2010; Mazursky-Horowitz et al 2017). Future work will also need to include parental ADHD symptoms, along with these basic processes, to examine their unique and interactive effects on parent and child behavior.…”
Section: Future Directionsmentioning
confidence: 99%
“…Within the broader parenting literature, several studies have shown that stronger parental WM predicts more positive parenting behaviors (Mazursky-Horowitz et al 2017) and less harsh parenting in the context of challenging child behaviors (Deater-Deckard et al 2010). Responsive parenting also correlates with stronger parental inhibitory control (Shaffer and Obradović 2017).…”
Section: Introductionmentioning
confidence: 99%